The status of and future research into Myalgic Encephalomyelitis and Chronic Fatigue Syndrome: the need of accurate diagnosis, objective assessment, and acknowledging biological and clinical subgroups - Twisk, Frank N. (Frontiers in Physiology, 2014)
Myalgic Encephalomyelitis (ME) was identified as a new clinical entity in 1959 and has been acknowledged as a disease of the central nervous system/neurological disease by the World Health Organisation since 1969. Cognitive impairment, (muscle) weakness, circulatory disturbances, marked variability of symptoms, and, above all, post-exertional malaise: a long-lasting increase of symptoms after minor exertion, are distinctive symptoms of ME. Chronic Fatigue Syndrome (CFS) was introduced in 1988 and was redefined into clinically evaluated, unexplained (persistent or relapsing) chronic fatigue, accompanied by at least four out of a list of eight symptoms, e.g. headaches and unrefreshing sleep, in 1994. Although the labels are used interchangeably, ME and CFS define distinct diagnostic entities. Post-exertional malaise and cognitive deficits e.g. are not mandatory for the diagnosis CFS, while obligatory for the diagnosis ME. “Fatigue” is not obligatory for the diagnosis ME. Since fatigue and other symptoms are subjective and ambiguous, research has been hampered. Despite this and other methodological issues, research has observed specific abnormalities in ME/CFS repetitively, e.g. immunological abnormalities, oxidative and nitrosative